O gênero Selenops Dufour in Latreille, 1819, no Brasil (Araneae - Selenopidae) - Duarte, Paula Frassinete Lins (1978)
Study of Brazilian Species of genus Selenops Latreille, 1819, concerning taxonomy aspects. This work was based upen material found in the following Institutions: Museu Nacionalda Universidade Federal do Rio de Janeiro (MN) Museu de Zoologia da Universidade de São Paulo (MZUSP) Instituto Butantan (IB) Instituto Básico de Biologia Médica e Agrícola da Universidade Estadual Paulista "Júlio de Mesquita" Campus de Bótucatu (IBBMA) Fundação Zoobotânica do Rio Grande do Sul (FZRS). The authorship of this genus was discussed and it was concluded that latreille was responsible for this genus based upon the ninth article of the International Code of Zoological Nomenclature. In Latin grammatical gender of the genus Selenops is femine.